‘Not rocket science’ or ‘No silver bullet’? Media and government discourses about MRSA and cleanliness - Koteyko, Nelya; Nerlich, Brigitte; Crawford, Paul; Wright, Nick (Oxford University Press, 2008)
Methicillin-resistant Staphylococcus aureus (MRSA), commonly called a superbug, has recently been a major political issue in the UK, playing a significant role in debates over health policy in the general election held in 2005. While science recognizes the lack of evidence with regards to the effectiveness of existing measures implemented to control and prevent MRSA, the UK media coverage is dominated by articles that appeal to common sense and practical experience calling for more government interventions to combat the bug. In this paper we explore how uncertainty surrounding the origin and spread of MRSA is portrayed in debates within the media and policy-circles to particular political ends. Using established techniques of discourse analysis and corpus linguistics, we examine the assumptions, judgements, and contentions that structure two discourses of MRSA: according to one discourse MRSA is ‘not rocket science’ and there are ‘simple’ ways of coping with the risk of infection, whereas according to another discourse MRSA is a more complex matter and there is ‘no silver bullet’. The analysis of different storylines through which specific ideas of ‘blame’, ‘responsibility’, and ‘urgency’ are attributed helps to explain how different ‘constructions’ of causes for the rise in MRSA emerged and led to discourses of blame and defence centred on cleanliness.